(untitled) (Zoological Records and Reviews, 2023)
Feeding ecology underpins the functional role of fish species within riverine food webs and determines the trophic linkages that regulate energy flow and nutrient cycling in freshwater ecosystems. Tropical rivers, characterised by high fish diversity, strong seasonal hydrological variability, and complex lateral connectivity between river channels and floodplain habitats, present distinctive feeding ecology challenges and opportunities for diverse fish communities. This study examines the feeding ecology of 84 freshwater fish species from the Godavari and Krishna river systems of peninsular India, using stomach content analysis, stable isotope analysis (delta13C and delta15N), and functional trait assessment at 18 sites sampled during monsoon flood and dry season low-flow periods over two years (2021-2023). Fish species are classified into eight feeding guilds based on stomach content analysis. Piscivores and invertivores dominate in terms of biomass contribution; algal grazers and detritivores are most species-rich. Stable isotope analysis reveals significant seasonal shifts in diet composition, with 38.4% of species showing ontogenetic diet shifts from invertivory to piscivory or herbivory. Invasive tilapia (Oreochromis niloticus) occupies a broad trophic niche that overlaps significantly with native species, with measured trophic overlap values exceeding 0.7 for 12 native species. Conservation implications of trophic disruption by invasive species and by water quality changes affecting food web structure are discussed.